KOMPETENSI DATA LIBRARIAN DALAM RESEARCH DATA MANAGEMENT: SYSTEMATIC LITERATURE REVIEW - Minarso, Christinia; Suprapto, Agung (BACA: Jurnal Dokumentasi dan Informasi, 2021)
This paper investigates the Data Librarian (DL) competencies in Research Data Management (RDM). Using the systematic literature review of paper published over the last ten years from 2010 to 2020 through databases subscribed by Brawijaya University Library. A total of 243 research articles yielded that meet the selection criteria and finally 15 studies were included in this study. The results obtained show that: (1) many articles discussing the competence of DL in the field of RDM are still written from and about librarians in academic libraries; (2) the most used methods of research are survey, case studies, and mixed-method; (3) the competence of DL presented varies each paper, however, the most common competencies are technical skills, followed by knowledge, non-technical skills, and abilities. This study provides an overview of libraries in Indonesia to be able to prepare and develop librarian competencies in their roles in the field of RDM.